Faktor–Faktor yang Mempengaruhi Niat Mahasiswa Akuntansi dalam Menggunakan Microsoft Excel untuk Menyelesaikan Tugas Kuliah - Yuwani, Dhita Rizkya; Mujilan, Agustinus; Purbandari, Theresia (JRMA | Jurnal Riset Manajemen dan Akuntansi, 2017)
In the modern era, the utilization of information technology systems in the world of education plays an important role, especially for accounting students in the completion of the task preparation of financial statements. The investigators suggest the use of microsoft excel among accounting students Universitas Katolik Widya Mandala Madiun is not optimum. This sudy aims to prove empirically the effect of personal factor and social factor to the intention by the accounting students in the use of microsoft excel to complete the coursework. This study uses primary data from questionnaires by respondents. Hypotheses were testing by SEM using PLS software. This study prove that intrinsic motivation, extrinsic motivation, and perceived usefulness have effect to the intention to use of microsoft excel to complete the coursework; intrinsic motivation has effect to the extrinsic motivation; intrinsic motivation has effect to the perceived ease of use; while the perceived ease of use has not affect to the intention to use of microsoft excel to complete the coursework; perceived ease of use has not effect to the extrinsic motivation; social factor has not affect to the perceived ease of use; social factor has not affect to the perceived usefulness.